Short-Term Effects of Mulligan Mobilization With Movement on Pain, Disability, and Kinematic Spinal Movements in Patients With Nonspecific Low Back Pain: A Randomized Placebo-Controlled Trial - Hidalgo, B.; Pitance, L.; Hall, Toby; Detrembleur, C.; Nielens, H. (Elsevier Inc, 2015)
Objective: The purpose of this clinical study was to compare the immediate- and short-term effects of lumbar Mulligan sustained natural apophyseal glides (SNAGs) on patients with nonspecific low back pain with respect to 2 new kinematic algorithms (KA) for range of motion and speed as well as pain, functional disability, and kinesiophobia. Methods: This was a 2-armed randomized placebo-controlled trial. Subjects, blinded to allocation, were randomized to either a real-SNAG group (n = 16) or a sham-SNAG group (n = 16). All patients were treated during a single session of real/sham SNAG (3 × 6 repetitions) to the lumbar spine from a sitting position in a flexion direction. Two new KA from a validated kinematic spine model were used and recorded with an optoelectronic device. Pain at rest and during flexion as well as functional disability and kinesiophobia was recorded by self-reported measures. These outcomes were blindly evaluated before, after treatment, and at 2-week follow-up in both groups. Results: Of 6 variables, 4 demonstrated significant improvement with moderate-to-large effect sizes (ES) in favor of the real-SNAG group: KA-R (P = .014, between-groups ES Cliff δ = − .52), pain at rest and during flexion (visual analog scale, P < .001; ES = − .73/− .75), and functional-disability (Oswestry Disability Index, P = .003 and ES = − .61). Kinesiophobia was not considered to be significant (Tampa scale, P = .03) but presented moderate ES = − .46. Kinematic algorithms for speed was not significantly different between groups (P = .118) with a small ES = − .33. All 6 outcome measures were significantly different (P ≤ .008) during within-group analysis (before and after treatment) only in the real-SNAG group. No serious or moderate adverse events were reported. Conclusion: This study showed evidence that lumbar spine SNAGs had a short-term favorable effect on KA-R, pain, and function in patients with nonspecific low back pain.